2022
DOI: 10.4314/ahs.v22i1.71
|View full text |Cite
|
Sign up to set email alerts
|

The predictive role of psychological toughness and adaptability on the actual well-being of mothers with handicapped children

Abstract: Background and Aim: Handicapped children cause psychological problems for mothers. As mothers' actual well-being is so important in the family and society, the aim of this research was to predict the role of psychological toughness and adaptability on the actual well-being of mothers with handicapped children. Materials and Methods: The research was descriptive correlational study with volunteer mothers of handicapped children (n=150). Data collection tools were: Ahwaz Kiamarsi et al. (1998) psychologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…We performed multiple regression analysis to identify the factors influencing parenting stress in NKR mothers; the results revealed that the explanatory power for the effects of hardiness and having four or more supporters on parenting stress was approximately 19%, while the factors with a fairly strong influence on parenting stress were hardiness and the number of supporters. Studies on the mothers of premature babies [ 29 ] and the mothers of children with special needs [ 30 ] lend support to the finding that psychological hardiness is a critical factor in parenting. Moreover, the bulk of parenting stress arose from parental factors and not child-related factors, highlighting the need for programs that improve hardiness, which would enable individuals to bolster their strength to control themselves and positively perceive stress as an opportunity for growth and development.…”
Section: Discussionmentioning
confidence: 97%
“…We performed multiple regression analysis to identify the factors influencing parenting stress in NKR mothers; the results revealed that the explanatory power for the effects of hardiness and having four or more supporters on parenting stress was approximately 19%, while the factors with a fairly strong influence on parenting stress were hardiness and the number of supporters. Studies on the mothers of premature babies [ 29 ] and the mothers of children with special needs [ 30 ] lend support to the finding that psychological hardiness is a critical factor in parenting. Moreover, the bulk of parenting stress arose from parental factors and not child-related factors, highlighting the need for programs that improve hardiness, which would enable individuals to bolster their strength to control themselves and positively perceive stress as an opportunity for growth and development.…”
Section: Discussionmentioning
confidence: 97%
“…The relationship with the physiotherapist emerges as one of the foremost sources of formal support for parents. Resilience appears to play a major role in the group of personal attributes that facilitate adaptation to disability and active engagement in therapy [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…The rest of the first issue of this 22 nd volume of African Health Sciences ranges from disability, surgery, to haematology and training 70 79 . Finally, we wish to thank all our partners, readers, volunteers, editorial and board teams, authors and reviewers.…”
mentioning
confidence: 99%